Why We Fight: War Comes to America - Capra, Frank (Elstree Hill Enetrtainment, 1945)
Poor image Duration: 01:06:00 The film's director Frank Capra served as a major in the U.S. Army Signal Corps and was commissioned by Army Chief of Staff General G. Marshall to make a series of films that would explain the government's policy to the troops hastily being assembled, trained, and sent overseas. The "Why We Fight" series is the supreme example of propaganda put out by the U.S. government during World War II. "War Comes to America" is the 7th and final film in the series. It sums up the historical and ideological information that was presented in greater detail during the other six films, reguritating a lot of material from "Prelude to War." It also delivers a powerful ideological statement about the mission and meaning of American democracy addressed both to domestic and international publics. It traces the shift in public opinion from isolationism towards supporting the Allies against the Axis forces brought about by Pearl Harbor. The film opens with children pledging allegiance to the flag, visits Lexington and Valley Forge, surveys the militant and idealistic history of the United States before embarking on a catalogue listings of states and nationalities contributing to the war effort. After this extended self-admiring prologue, the film recaps the major events of the War, starting with the 1931 invasion of Manchuria by the Japanese until the Japanese attack on Pearl Harbor in 1941 and America's entry into the war. Characteristically, the last three films of the Capra's series concentrate a lot more on the virtues of their Allied armies than on the atrocities of the Axis foes. Arguably, the events of the WWII are used as a backdrop against which the virtues of American society can be effectively celebrated - e.g. racial tolerance (the Japanese are conventiently unmentioned), freedom, solidarity, etc.